Penerapan Terapi Pijat Refleksi Untuk Menurunkan Tekanan Darah pada Lansia dengan Hipertensi di RSUD dr. Soeratno Gemolong - Mareta Kumala Sari; Erika Dewi Noorratri; Fitria Purnamawati (Yayasan Literasi Sains Indonesia, 2023)
Hypertension is a cardiovascular disease, in general, it has no known complaints, so it is known as the silent killer, characterized by an increase in systolic blood pressure of ≥ 140 mmHg and diastolic ≥90 mmHg. One of the factors in the occurrence of hypertension is the age factor, hypertension in the elderly is more important to be treated because of the pathogenesis, course of the disease, and its management. Non-pharmacological treatment can overcome hypertension and is useful for improving the quality of life of patients and preventing complications, one of the non-pharmacological actions is massage therapy (reflexology). To find out the results of the implementation regarding giving reflexology therapy to reduce blood pressure in the elderly with hypertension. using a case study design, subjects in 2elderly with hypertension who were treated at RSUD dr. Soeratno Gemolong, using a tensimeter to measure blood pressure before and after therapy. obtained an average decrease in systolic blood pressure of 5.2 mmHg and an average decrease in diastolic blood pressure of 5 mmHg after being given reflexology massage therapy.